Global Financial Inclusion and Consumer Protection Survey, 2017 Report - World Bank Group (World Bank, Washington, DC, 2017)
Financial sector authorities increasingly prioritize financial inclusion and financial consumer protection, alongside existing priorities of stability and integrity. An enabling environment that facilitates competition, promotes innovation and the use of technology, addresses risks in a proportionate manner, and empowers financial consumers to make informed choices is critical to improving financial inclusion and consumer protection. The 2017 Global Financial Inclusion and Consumer Protection (FICP) Survey tracks the prevalence of key policy, legal, regulatory, and supervisory approaches to advancing financial inclusion and consumer protection. The 2017 Global FICP Survey covers key topics related to the enabling environment for financial inclusion and financial consumer protection, including national financial inclusion strategies, the issuance of e-money by nonbanks, agent-based delivery models, simplified customer due diligence, institutional arrangements for financial consumer protection, disclosure, dispute resolution, and financial capability. The 2017 Global FICP Survey covers regulated retail institutions that provide standard loan, deposit, or payment services. Financial sector authorities in 124 jurisdictions – representing 141 economies and more than 90 percent of the world’s unbanked adult population – responded to the 2017 Global FICP Survey. This report presents main findings from an analysis of those responses.